Early general movements are associated with developmental outcomes at 4.5–5 years. (September 2020) - Olsen, Joy E.; Cheong, Jeanie L.Y.; Eeles, Abbey L.; FitzGerald, Tara L.; Cameron, Kate L.; Albesher, Reem A.; Anderson, Peter J.; Doyle, Lex W.; Spittle, Alicia J.
Abstract: Background: Prechtl's general movements assessment (GMA) post-term has high predictive validity for cerebral palsy, but less is known about whether earlier GMA, including before term, are associated with other developmental problems. Aims: To examine the relationships between GMA prior to term and at term-equivalent, with developmental outcomes at 4.5–5 years' corrected age. Study design: Prospective cohort study. Subjects: 122 very preterm infants born <30 weeks' gestation and 91 healthy term controls. Outcome measures: GMA (categorised as 'normal' or 'abnormal') were assessed at <32, 32–33 and 34–36 weeks' postmenstrual age for the preterm infants, and at term-equivalent for both groups. Children were assessed at 4.5–5 years' corrected age using the Movement Assessment Battery for Children-2nd edition (MABC-2), Pediatric Evaluation of Disability Inventory-Computer Adaptive Test (PEDI-CAT), Pediatric Quality of Life Inventory (PedsQL), Little Developmental Coordination Disorder Questionnaire (Little DCD-Q) and Wechsler Preschool and Primary Scale of Intelligence-IV (WPPSI-IV). Results: Prior to term, abnormal GMA at the first two timepoints were associated with lower scores on the Little DCD-Q, and abnormal GMA at the second and third timepoints with lower quality of life scores and PEDI-CAT mobility domain scores. Abnormal GMA at term-equivalent were associated with lower MABC-2, mobility and quality of life scores for preterm infants, and worse social/cognitive domain scores for both groups. Conclusions: Abnormal GMA prior to term and at term-equivalent are associated with worse motor, functional and cognitive outcomes at 4.5–5 years' corrected age, and may be useful to identify infants for developmental surveillance/early intervention. Highlights: Abnormal general movements before term are associated with worse functional outcomes in early childhood Abnormal general movements at term age are associated with worse motor and functional outcomes for children born very preterm Abnormal general movements at term age are associated with worse social/cognition scores for term-born children